Representation of Inequality and Patriarchal Power in My Brilliant Friend - Nikita Priskila Tamara Siagian; Ruly Indra Darmawan (Universitas Islam Negeri Palopo, 2026)
This article analyzes how gender inequality and patriarchy are portrayed in the novel My Brilliant Friend by Elena Ferrante. The writer especially focuses on the main character's experience, but also involves other characters in the novel. For the method, we will use a qualitative descriptive approach through a feminist lens, drawing on Betty Friedan's work. The writer finds that the novel My Brilliant Friend not only centers on an intimate and complex friendship between two girls but also reveals a deeper layer of social critique regarding the pervasive, embedded patriarchal issues and gender inequality in their daily lives. Through the experiences of Elena Greco (Lenu) and Raffaella Cerullo (Lina or Elena called her Lila), the narrative vividly depicts how societal expectations, limited female education, domestic oppression, and male dominance systematically shape and often limit women's autonomy. By employing Betty Friedan’s feminist perspective, this article concludes how the character's struggles reflect broader issues of women’s oppression, identity formation, and resistance within a patriarchal society. Thus, the novel becomes not only a story of personal growth and friendship but also a powerful representation of the silent yet persistent injustices faced by women, illustrating that acts of resilience and self-awareness are crucial forms of resistance against deeply rooted gender inequality.